Echocardiographic Screening for Transcatheter Edge-to-Edge Mitral Valve Repair: Correlation Between Transthoracic and Transesophageal Assessment - Michela Bonanni; Fausto Pizzino; Giovanni Benedetti; Rosangela Capasso; Rachele Manzo; Giuseppe Iuliano; Giancarlo Trimarchi; Andreina D’Agostino; Umberto Paradossi; Alessia Gimelli; Sergio Berti; Massimiliano Mariani (Journal of Cardiovascular Development and Disease)
Background: In patients with significant mitral regurgitation (MR) undergoing transcatheter edge-to-edge repair (M-TEER), assessment of mitral valve (MV) anatomy is essential. While transthoracic echocardiography (TTE) is the initial diagnostic tool, transesophageal echocardiography (TOE) provides better anatomical details. The study aims to assess whether TTE is as effective as TOE in selecting patients with severe MR who are eligible for M-TEER. Methods: From January to December 2024, patients with severe MR eligible for TEER were enrolled at the Fondazione Monasterio Heart Hospital, Italy. They underwent a comprehensive TTE and TOE examination. Cardiologists assessed the severity of MR and valve anatomy using specific protocols. Measurements included MV area, MV gradient, posterior leaflet length, fossa ovalis high, presence of fails, clefts, and calcifications. Three levels of anatomic complexity were defined to determine eligibility for TEER. Results: The study includes 40 patients with severe MR. The correlation between TTE and TOE for key parameters was strong, with coefficients ranging from 0.734 to 0.901, indicating high agreement between the two methods. The comparison of categorical features showed high agreement between TTE and TOE in detecting critical MV conditions, with kappa values ranging from 0.717 to 0.930. The agreement for classifying patients as suitable for M-TEER was 87.5%, indicating moderate consistency between the two methods. Conclusions: TTE may be a viable alternative to TOE for assessing MV anatomy and function before M-TEER in MR patients, especially in high-volume centers. While TTE strongly correlated with TOE for most parameters, TOE was superior for some features. Further research is needed to refine the clinical application of TTE and to define patient selection criteria for its use as the primary imaging modality for pre-procedural M-TEER screening.